1999
DOI: 10.1046/j.1469-8137.1999.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between photosynthesis, nitrogen and leaf structure in 14 grass species and their dependence on the basis of expression

Abstract: The relationships between leaf structure, nitrogen concentration and CO # assimilation rate (A) were studied for 14 grass species grown in the laboratory under non-limiting nutrient conditions. Structural features included leaf thickness and density, and the proportion of leaf volume occupied by different types of tissue (mesophyll, epidermis, vessels and sclerenchyma). Relationships were assessed for data expressed per unit leaf area and fresh mass. The latter was found to be closely related to leaf vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
2
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 34 publications
4
81
2
4
Order By: Relevance
“…A number of studies have documented large-scale patterns of, and potential driving forces for plant functional traits (Castro-Díez et al 2000;Garnier et al 1999;He et al 2009;Niinemets 2001;Reich and Oleksyn 2004;Reich et al 1997;Shipley and Lechowicz 2000;Wright et al 2004). These efforts have revealed that (1) regardless of biome, life form, or phylogenetic history, the scaling of bivariate and multiple trait relations are generally similar and predictable (He et al 2009;Reich and Oleksyn 2004;Reich et al 1997;Wright et al 2004), (2) across biomes, species, and research sites, the modulation of leaf traits by climate is surprisingly modest , although some significant patterns can be detected, and (3) differences in key attributes, including life-form, phenology, phylogenetic history, and ecological strategies, are related to variation in leaf traits (Reich et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have documented large-scale patterns of, and potential driving forces for plant functional traits (Castro-Díez et al 2000;Garnier et al 1999;He et al 2009;Niinemets 2001;Reich and Oleksyn 2004;Reich et al 1997;Shipley and Lechowicz 2000;Wright et al 2004). These efforts have revealed that (1) regardless of biome, life form, or phylogenetic history, the scaling of bivariate and multiple trait relations are generally similar and predictable (He et al 2009;Reich and Oleksyn 2004;Reich et al 1997;Wright et al 2004), (2) across biomes, species, and research sites, the modulation of leaf traits by climate is surprisingly modest , although some significant patterns can be detected, and (3) differences in key attributes, including life-form, phenology, phylogenetic history, and ecological strategies, are related to variation in leaf traits (Reich et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Leaves acclimated to shade tend to have higher net photosynthetic rates at lower light levels and a lower light compensation point compared with sun leaves (Givnish, 1988). To compare plants/species with different leaf thicknesses, previous studies have used mass integrated photosynthesis as a proxy to assess the photosynthetic efficiency of plants with different volumes of photosynthetic tissues (Garnier et al, 1999;Evans and Poorter, 2001;Wright et al, 2001). Previous studies investigating developmental acclimation have focused primarily on the effect of light intensity, with less emphasis given to the effect of dynamic light during growth, like that experienced under a natural environment.…”
mentioning
confidence: 99%
“…These differences in SWC between treatments are of considerable magnitude, which could be demonstrated by an estimate of its succulence, in approximate terms. Assuming that fresh mass value of an organ can be used as a proxy for their volume (Garnier et al, 1999) . These values are between ten and fifteen times greater than those corresponding in leaves (Figure 4).…”
Section: Resultsmentioning
confidence: 99%